PENGARUH GREEN MARKETING, BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN MEREK ADES DI SAMARINDA - Tika Rahmatika (University of Widya Gama Mahakam Samarinda, 2021)
This study aims to determine the effect of Green Marketing, Brand Image and Brand Trust on the purchase decision of Ades branded bottled drinking water in Samarinda City. The number of samples is 100 respondents who are Ades consumers in Sarinda City. The data collection method used a questionnaire. The sampling technique in this study used a purposive sampling technique. The data analysis method uses multiple linear regression with the F test and T test to determine the joint and partial effect using the SPSS ver 23 program. have a positive and significant influence on purchasing decisions. The results of statistical tests state that together Green marketing, Brand Image and Brand Trust have a positive and significant influence on purchasing decisions.